The Factors Affecting Soybean Production in Indonesia Using Robust Regression with Least Median of Squares (LMS) Estimation - Ratri, Aninda Puspa; Susanti, Yuliana; Slamet, Isnandar (Nusantara Science and Technology Proceedings, 2021)
Soybean is a product with a source of protein that improves the nutrition of Indonesians. The demand for soybeans is increasing, but the domestic production is not sufficient, so that the soybean production in Indonesia must be increased. This study aims to determine the influential factors on soybean production in Indonesia. The data of soybean production in Indonesia had outliers. Outliers cause the residual is not normally distributed so that the assumption of normality is violated. This problem was solved using robust regression. The estimation used was the Least Median of Squares because this estimation has a quite large breakdown point value. The results of the study show that the soybean production in Indonesia was influenced by the field area, the number of soybean seeds, and rainfall. The most influential factor on soybean production is the number of soybean seeds, field area, and rainfall. The attempts that must be conducted by the government to increase soybean production are by having socialization about soybean cultivation and ensuring the availability of soybean seeds in Indonesia.